Implementasi Manajemen Sosial dalam Kampanye Gizi: Kacang Merah sebagai Alternatif Nutrisi Pencegah Stunting - Anam, Chaerul; Liddini, Laily; Nita, Siska Yulia; Fadillah, Nurul Afit; Attabi, Muhammad Fatih (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Stunting is a chronic nutritional problem that affects the growth and development of children, especially toddlers. One effective prevention effort is through nutritional education by introducing nutritious local food sources, such as red beans, which are rich in protein, fiber, and iron. This community service activity aims to increase public understanding, especially parents, regarding the importance of balanced nutrition and the use of red beans as an alternative nutrition in preventing stunting. The method used is Asset-Based Community Development (ABCD) through interactive counseling, demonstrations of red bean-based food processing, and evaluation of participant understanding before and after the activity. The results showed a significant increase in public nutritional knowledge and increased children's interest in consuming red beans. Local food-based nutritional education has proven to be an effective strategy in increasing public awareness of stunting prevention.